A homochiral magnet based on D3 symmetric [(NaO3)Co3] clusters: from spontaneous resolution to absolute chiral induction1. Issue 24 (25th March 2015) - Yao, Ru-Xin; Cui, Xin; Wang, Jun; Zhang, Xian-Ming
<x xml:space="preserve">Abstract</x> A pair novel 3D chiral magnets have been synthesized using the achiral ligand imidazole-4-acrylate via spontaneous resolution, in which the D3 symmetric chiral [(NaO6)Co3] clusters act as nodes. By using chiral induction agent, they are driven to controllable homochiral crystals.